PA5001 gene involves in swimming motility and biofilm formation in Pseudomonas aeruginosa. (July 2020) - Li, Yingli; Xia, Huiming; Bai, Fang; Song, Xuyang; Zhuang, Luning; Xu, Haijin; Zhang, Xiuming; Zhang, Xiuming; Qiao, Mingqiang
Abstract: Pseudomonas aeruginosa is a nosocomial human pathogen causing infections in immunocompromised patients. To explore new genes involved in P. aeruginosa swimming motility, Mu transposon mutagenesis library was screened for isolates with altered swimming motility. Eleven nonmobile mutants were identified. Sequence analysis shows the nonmobile phenotype of one isolate was attributed to the inactivation of PA5001 gene. PA5001 knockout mutant based on the PAK lab strain also displayed comparable phenotypes suggesting the universal gene function regardless of strain. Exotic PA5001 gene fragment provided on expressing plasmid was capable of storing nonmobile phenotype of PA5001 mutant, suggesting the functional involvement of PA5001 gene on bacterial swimming. Impact of PA5001 inactivation on biofilm formation was examined, as adhesion and interaction during biofilm formation is highly dependent of bacterial mobility. The result shows that normal architecture of biofilm was disrupted in the mutant. Complementing by exotic PA5001 gene fragment resulted in the restoration of biofilm phenotype. Our results provide evidences suggesting the functional participation of PA5001 gene in bacterial mobility and biofilm formation. The critical function by PA5001 in bacterial motility and biofilm might serve as hint for the novel target for the treatment of chronic infections caused by P. aeruginosa. Highlights: One nonmobile mutant isolate screened from Mu transposon mutagenesis library was identified to have PA5001 gene inactivation. PA5001 knockout mutant based on the PAK lab strain also displayed comparable phenotypes suggesting the universal gene function regardless of strain. Exotic PA5001 gene fragment provided on expressing plasmid was capable of storing nonmobile phenotype of PA5001 mutant, suggesting the functional involvement of PA5001 gene on bacterial swimming. Normal architecture of biofilm was disrupted in the PA5001 mutant strain. Complementing by exotic PA5001 gene fragment resulted in the restoration of biofilm architecture.